Proton Pump Inhibitor-Induced Hypomagnesemia: A Rare, Potentially Fatal Complication - Pawlukiewicz, Alec J (Cureus, 2020)
Hypomagnesemia has been associated with a variety of abnormalities, including neurological, cardiac and secondary electrolyte abnormalities. We present the case of a 77-year-old male who presented to the emergency department with tremor and difficulty walking and was found to have severe hypomagnesemia necessitating hospital admission. After thorough workup, the patient's hospital course concluded that the profound hypomagnesemia was secondary to proton pump inhibitor use. Physicians should be aware of proton pump inhibitor-induced hypomagnesemia as a rare, but easily correctable etiology of hypomagnesemia.